Television in Conflict: The Romanian Revolution as Audiovisual Experiment - Morozov, Victor (Trinity College Dublin. School of Creative Arts. Discipline of Film, 2026)
This dissertation attempts to renew and expand the extant interpretations of the Romanian Revolution understood in its media dimension. Although numerous contributions have attempted to produce critical knowledge on this topic, we argue that the vast majority has been relying on the same restrained (and restrictive) mass of footage, thus inevitably leading to the ossification of this field of study. By adopting an innovating methodological framework based on a so far critically under-developed notion derived from French film theory, `the trademark image, this research project aims to both synchronise the case study of the revolution with contemporary theoretical debates, and to reinvigorate interest in this particular topic in and of itself. Our thesis is informed by a flexible approach, whereas its main objectives remain similarly open to transversal interrogations. Given its original scope, it wishes to be both a critical re-actualisation of past knowledge from a seminal moment in the cultural history of media, and a speculative overture towards a larger, inclusive methodology which can aptly question present-day realities as well as unknown, neglected or forgotten aspects of the past. One of the main points of interest of this dissertation, with regard to its case study, is the inherent transnational perspective which makes use of vernacular literature as well as highly updated bibliography belonging to a variety of fields of study and multiple languages (the main ones being English and French). As such, this research project will allow the apparently local reality of the Romanian Revolution to raise potential interest within the larger academic community. This intention is further substantiated by the corpus of the work itself: characterised by an across-media approach one that positions television as its primary object while drawing on photography and cinema as genealogical and comparative frameworks , this dissertation operates both with strictly theorised frameworks such as an overview of the indexical paradigm in photography and cinema, using a variety of discourses and relevant literature combining theological, ontological, and technical understandings of the medium and with close textual analyses of the actual footage. Unlike previous attempts to conceptualise the revolution in terms of a purely media event, we have adopted a meticulous method that involved consulting all footage accessible within the current state of the Romanian Television Archives making no a priori discrimination between material that had been widely circulated and material that remained critically overlooked. Naturally, this posed several implications on the general optics of our research, which favoured a focus on counter-imagery that has so far been overlooked by previous research. Moreover, our motivation has not been a detectivist one: our methodological openness towards images neither fetishising them as transparent proofs of truth, nor automatically dismissing them as inevitable vehicles of manipulation guided our analytical approach. This methodological even-handedness should not, however, be confused with political neutrality: as the research makes progressively clear, this project proceeds from a committed, politically situated perspective, seeking to restore overlooked counter-images to critical visibility and to argue for the emancipatory potential of experimental televisual practices. Drawing on this situated attitude, we have chosen to examine the audiovisual circuits which, at that moment in time, contributed to the creation of dominant narratives, and to uncover their aesthetic and ideological mechanisms. Finally, by separating trademark images those audiovisual samples that have been retained by public conscience by virtue of their emblematic, easily decodable character from their opposites counter-images which express alternative meanings and operate according to different regimes of visibility , we have aimed to unveil multiple competing discourses at play during the revolution, positing it as a complex, irreducible generator of footage that can serve in order to illuminate current conflicts and their respective media coverages.
APPROVED
Keywords: television; archives; trademark images; counter-images; Romania; Serge Daney; indexicality; revolution